AWARENESS AND UTILIZATION OF DIGITAL RESOURCES IN AGRICULTURAL UNIVERSITIES: A STUDY OF FACULTY AND RESEARCH SCHOLARS - Prasad, Navin; Dabas, Sheela (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The integration of digital resources in agricultural universities has become essential for academic and research excellence. This study aims to assess the awareness and utilization of digital resources among faculty members and research scholars in agricultural institutions. By analyzing factors such as accessibility, usage patterns, challenges, and the impact of digital tools on academic productivity, this research provides insights into how digital transformation is shaping agricultural education and research. The study employs a mixed-methods approach, including surveys and interviews, to gather comprehensive data from selected agricultural universities. Statistical analysis using SPSS software was conducted to derive meaningful insights from the collected data. The results are represented through tables, graphs, and pie charts for better visualization. Key findings reveal that while digital resources are widely recognized as essential, challenges such as digital literacy gaps and infrastructure limitations hinder their full potential. This research offers recommendations for improving digital literacy, enhancing infrastructure, and fostering a more inclusive digital environment. The study contributes to the ongoing discourse on educational technology and aims to bridge the digital divide in agricultural academia. Keywords Digital resources, agricultural universities, faculty, research scholars, academic productivity, digital literacy, information technology, research tools, digital transformation, higher education.